Regulation of Vascular Injury and Repair by P21-Activated Kinase 1 and P21-Activated Kinase 2: Therapeutic Potential and Challenges - Chuting Han; Mengying Zhu; Yiting Liu; Yan Yang; Jun Cheng; Pengyun Li (Biomolecules)
The PAK (p21-activated kinases) family is a class of intracellular signal transduction protein kinases that regulate various cellular functions, mainly through their interactions with small GTP enzymes. PAK1 and PAK2 in the PAK kinase family are key signal transduction molecules that play important roles in various biological processes, including morphological changes, migration, proliferation, and apoptosis, and are involved in the progression of many diseases. Abnormal expression or dysregulation of PAK1 and PAK2 may be associated with several diseases, including cancer, neurological diseases, etc. The current research mainly focuses on studying the role of PAK and PAK inhibitors in the regulation of cancer progression, but relatively few reports are available that explore their potential role in cardiovascular diseases. Vascular injury and repair are complex processes involved in many cardiovascular conditions, including atherosclerosis, restenosis, and hypertension. Emerging research suggests that PAK1 and PAK2 have pivotal roles in vascular endothelial cell functions, including migration, proliferation, and angiogenesis. These kinases also modulate vascular smooth muscle relaxation, vascular permeability, and structural alterations, which are critical in the development of atherosclerosis and vascular inflammation. By targeting these activities, PAK proteins are essential for both normal vascular physiology and the pathogenesis of vascular diseases, highlighting their potential as therapeutic targets for vascular health. This review focuses on recent studies that offer experimental insights into the mechanisms by which PAK1 and PAK2 regulate the biological processes of vascular injury and repair and the therapeutic potential of the current existing PAK inhibitors in vascular-related diseases. The limitations of treatment with some PAK inhibitors and the ways that future development can overcome these challenges are also discussed.